Phonology Acquisition in Nepal: A Preliminary Study - Prabha Dawadee (Science-res Publishing, 2021)
The process of speech and language development in children is an effortless and basic human skill. As the child acquires language, they acquire a sign system that bears an important relationship to both cognitive and social aspects of their life.  Every language has its own phonological system so it is necessary to develop language-specific articulatory skill acquisition norms. The aim of the study was to delineate the phonology acquisition in typically developing Nepali-speaking children between the ages 3 and 7.